SUMEDANG EARTHQUAKE RELOCATION PERIOD DECEMBER 31, 2023 – JANUARY 4, 2024 USING DOUBLE DIFFERENCE METHOD - Maftuha, Ninda; Zera, Tati; NurFaizi, Mochamad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
On December 31, 2023, an earthquake occurred in Sumedang with a magnitude of M=4.8. The location of the epicenter is at coordinates 6.85'S and 107.94'E, or precisely on land at a distance of 2 km northeast of the center of Sumedang City, with a hypocenter of 5 km. This earthquake is categorized as a shallow earthquake (M